UPAYA PENINGKATAN SISTEM MANAJEMEN MUTU DALAM PENERAPAN (ISO 9001, 2015) DI PT. DINAR MAKMUR - Afif Hakim; Ni Wayan Puji E (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2020)
The problem with the company is the increase in non-conformance findings in the internal ISO audit report which is very significant, namely as many as 20 findings related to clause 7.2 of controlling information documents within a period of 6 months. Therefore, the main problem raised in this analysis is how to reduce the findings of non-conformities in the results of internal audit and document management at PT. Dinar Makmur uses fishbone diagrams, PLAN – DO – CHECK – ACTION (PDCA) cycles and provides training for employees to employee evaluations until the findings of the company's internal audit results decline. After that, a calculation of the improvements that have been made is carried out by adding up the clause findings obtained after the audit and divided by the number of sections/departments multiplied by the number of points audited. So the results of the increase in the value of the audit as much as 12% success rate from before the repair. After improvements were made, there was a decrease in findings in the previous period January-June 2018 as many as 40 findings and in the July-December 2018 period as many as 30 findings, and the difference in the decline that has been achieved is 10 findings.